Nie mehr zurück in dieses Land : Augenzeugen berichten über die Novemberpogrome 1938 - Gerhardt, Uta 1938-; Karlauf, Thomas 1955- (Propyläen-Verl, 2009)
"November 9th, 1938, is widely seen as a violent turning point in Nazi Germany's assault on European Jewry. Now, 70 years after the Night of Broken Glass, Uta Gerhardt and Thomas Karlauf have unearthed fascinating and disturbing personal chronicles, written soon after the nights of terror orchestrated and encouraged by the Nazi regime. In 1939, Harvard sociologist Edward Hartshorne gathered stories from hundreds of Jews who had fled Germany in the wake of "Kristallnacht". Those accounts have never been published. Until now. This unique collection provides a broad, authentic and distinctive description of the Nazi-incited Night of Broken Glass in Germany and Austria. A unique historical find, a treasure for all generations to come, a memory not to be forgotten"--Publisher's website